Rörande polysem belägenhet - Darnell, Ulrika Kvist (Nordiske Studier i Leksikografi, 2001)
In my work with Svensk Konstruktionsordbok, the verbs sitta ("sit"), stå ("stand") and ligga ("lie") ha ve shown to be problematic to handle because of the many ways they are used in the many phrases they appear in. In this paper, where I focus on the verb ligga ("lie"), I discuss the possibility of using the term polysemy only in two strict senses; extended meanings and metaphorically transferred meanings. By rather strict constraints (function and productiveness) of these types of meaning variation, I try to achieve a systematic and efficient tool for structuring the descriptions of these verbs. In the end of this discussion I suggest a polysemic mode! for these verbs, where the extended meanings form a base from which metaphorically transferred meanings may emerge.